Cross-Cultural Validation and Psychometric Properties Test of the Healthy Lifestyle Intention Scale for University Students - Kähkönen, Outi; Engblom, Janne R.K.; Lau, Ying; Wong; Eliza Lai Yi; Tian, Cindy Yue; Cheung; Annie Wai Ling; Chan; Ho Hin Henry; Oikarinen, Anne Kaarina (John Wiley and Sons Inc, 2026)
Background: University students are internationally recognized as a population at risk due to unhealthy lifestyle behaviors and elevated health risks. Supporting positive behavioral change requires understanding their intentions to adopt healthier habits. This study aimed to psychometrically evaluate and culturally validate the healthy lifestyle intention scale (HLIS) in three countries and regions.
Methods: A cross-sectional methodological study was conducted in 2023 among university students in Finland (n = 753), Singapore (n = 750), and Hong Kong, China (n = 767). The HLIS was developed based on the Adherence to Treatment of Patients with Chronic Disease Instrument. Psychometric evaluation included Spearman's ρ, Cronbach's ɑ, and both exploratory and confirmatory factor analyses.
Results: Findings from all three countries and regions indicated that Spearman's ρ values ranged from weak to high across the dimensions of self-readiness (0.23–0.69), family support (0.42–0.78), peer support (0.48–0.80), and social media influence (0.48–0.80). Cronbach's ɑ values demonstrated acceptable internal consistency (0.41–0.92). Structural validity was supported by confirmatory factor analysis. While the Finnish model suggested a need for further refinement (comparative fit index [CFI] = 0.81, root mean square error of approximation [RMSEA] = 0.11), the models for Singapore (CFI = 0.92, RMSEA = 0.07) and Hong Kong, China (CFI = 0.92, RMSEA = 0.07) showed strong fit indices.
Conclusion: The current version of the HLIS demonstrates promising psychometric properties for assessing health-related behavioral intentions among university students in a cross-cultural context. Further validation with more diverse international samples is recommended.